2014
DOI: 10.1007/s00787-014-0533-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum matrix metalloproteinase-9 levels and severity of symptoms in boys with attention deficit hyperactivity disorder ADHD/hyperkinetic disorder HKD

Abstract: The serum levels of matrix metalloproteinase-9 (MMP-9) in neuropsychiatric disorders of adults have been widely investigated. So far, no studies have been conducted on the relationship of MMP-9 and cognitive domains in children with two phenotype models, attention deficit/hyperactivity disorder and hyperkinetic disorder (ADHD/HKD). The aim of this research was to evaluate and test the hypothesis that serum MMP-9 levels are associated with the severity of symptoms in children with ADHD/HKD and to compare the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
(110 reference statements)
1
4
0
Order By: Relevance
“…45 Both animal experiments and human studies have indicated that BDNF levels are affected by conditions that are described as disruptions in the control of impulses. 46,47 In addition, another article also reported that the serum level of MMP-9 may be associated with impulsivity, 48 which would be consistent, though indirectly, with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…45 Both animal experiments and human studies have indicated that BDNF levels are affected by conditions that are described as disruptions in the control of impulses. 46,47 In addition, another article also reported that the serum level of MMP-9 may be associated with impulsivity, 48 which would be consistent, though indirectly, with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…A study on the northeastern population in China showed that the serum level of MMP-9 in cerebrospinal fluid (CSF) was increased in tick-borne encephalitis. It has been suggested that there is a correlation between MMP-9 serum levels and the severity of symptoms in the attention deficit/hyperactivity disorder and hyperkinetic disorder (ADHD/HKD) (Kadziela-Olech, Cichocki, Chwiesko, Konstantynowicz, & Braszko, 2015). Increased concentration of MMP-9 in the serum of patients with cognitive impairment, independently of established conventional risk factors in the short-term phase of IS has also been reported (Zhong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Signs of improvement have been seen but the rate of progress is still not good enough [14]. Waiting time reduction initiatives should be considered to answer the question “wait time to what?”, with the aim that shortened waiting time should improve the quality of delivered care, obtaining better clinical outcomes that must be monitored [37].…”
Section: Discussionmentioning
confidence: 99%